So many scenarios in herpetic eye disease (Ukrainian Journal of Ophthalmology, 2024)
Human herpes infections are a major cause of morbidity worldwide. Herpes Simplex Virus (HSV) and Varicella Zoster Virus (VZV) are frequent causes of ocular pathology. Ocular herpes is a recurrent disease, and its complications may lead to blindness. Herpetic viral infection is characterized by its ability to remain latent in the nervous system. Reactivation from the ophthalmic branch of the trigeminal ganglion may lead to recurrent attacks.Ocular herpes is a disastrous disease causing suffering and anxiety to millions of people, and also represents important economic burden. Recently the incidence of varicella zoster virus (VZV) is increasing for unknown reasons. Published data demonstrate also that more that 50% of patients with ocular and systemic manifestation of VZV are younger than 60 years and immunocompetent. We analyze retrospectively 160 consecutive patients with ocular herpes treated at our referral specialized eye hospital, and proposed original approach to different scenarios of disease development.
Keywords: latent herpetic infection; antiherpetic drugs; differential diagnosis HSV/VZV; keratoplasty in corneal perforation; epidemiology of herpetic eye disease (HED)